Impact of noninsulin-dependent diabetes mellitus (level of control) on sex hormone profile and erectile function - Abdullah A. Khawaji; Hossam S. El-Tholoth; Muath A. Albarakati; Bander A. Binjabaan; Abdulaziz Alzahrani; Abdulmajeed Althobity; Abdulmalik Almardawi; Khaled Bedaiwi; Mussa AlNuami (Urology Annals)
Introduction: Type 2 diabetes mellitus (T2DM) is a well-established risk factor for erectile dysfunction (ED); the precise impact of glycemic control on male sexual function, including hormonal profiles, remains to be fully elucidated. This study aims to investigate the specific relationship between the degree of glycemic control in T2DM patients and the severity of both hormonal imbalances and ED. Methodology: A comparative study between two arms – relatively controlled and uncontrolled type 2 diabetic men. We considered a relatively controlled diabetes mellitus (DM), patient with glycated hemoglobin (HbA1c) of 7.9 mmol/L or less. Laboratory results for type 2 diabetic men presenting with ED were studied after stratifying them into the two groups – relatively controlled DM (HBA1c of 7.9 mmol/L or less) and uncontrolled DM (HBA1c equal to or more than 8 mmol/L). Retrieved data include patient’s demographics, body mass index (BMI), hormonal profile, Complete Blood Count (CBC), lipid profile, prostate-specific antigen (PSA), urate, Vitamin D level, and the severity of ED as assessed by the International Index of Erectile Function (IIEF) scores. Statistical analysis was done to compare between the two groups using SPSS version 20. P < 0.05 was considered statistically significant. Results: This study found a significant association between poor glycemic control (HbA1c ≥8%) and ED in diabetic men (P < 0.0001). Longer diabetes duration correlated with both ED and poor glycemic control, suggesting a potential causal link. Well-controlled diabetics had lower BMI (P = 0.001), higher free testosterone (FT) (P = 0.0002), lower sex hormone-binding globulin (SHBG) (P = 0.0001), and higher IIEF scores (P < 0.0001) compared to the poorly controlled group, indicating better erectile function and potential benefits of weight management and improved testosterone availability. While follicle-stimulating hormone and luteinizing hormone levels were not significantly affected, Vitamin D levels were higher in the well-controlled group (P = 0.0002), suggesting a potential role for Vitamin D in ED, although further investigation is needed. Cholesterol, low-density lipoprotein, high-density lipoprotein, triglycerides, PSA, thyroid-stimulating hormone, and T4 levels did not show significant differences but might warrant further exploration. Conclusion: This study demonstrates an association between poor glycemic control and impaired erectile function in diabetic men. Lower FT levels, elevated SHBG, and increased BMI were observed in the poorly controlled group, potentially contributing to ED. Conversely, good glycemic control correlated with improved erectile function, potentially due to higher FT availability and Vitamin D levels.